Parametric optimalization of submerged fermantation conditions for xylanase production Bacillus cereus BSA1 through Taguchi Methodology - Mandal, Asish; Kar, Sanjay; Dutta, Tapan; Pati, Bikas Ranjan; Mondal, Keshab Chandra; Mohapatra, Pradeep Kumar Das (Acta Biologica Szegediensis, 2015)
Extracellular xylanase production of Bacillus cereus BSA1 was optimized under submerged fermentation using Taguchi orthogonal array (OA). An L18 layout of OA was constructed at three-levels of six factors, i.e. temperature, pH, and xylan, Na2HPO4, NH4NO3 and NaCl concentrations, influencing the xylanase synthesis. The enzyme production was studied in 18 parallel batch systems using different levels of each factor. The results were processed with Qualitek-4 software using ‘bigger is better’ quality character, and combination of 35 oC; pH 6.0; and xylan 0.5; NH4NO3 0.5, Na2HPO4, 0.1; NaCl 0.05 concentrations (in w/v %) with a predictive xylanase production of 7.404 U/ml was obtained. Fermentation experiment was performed for further validating the statistical output, and it resulted 10.24% in the xylanase yield (from 6.44 U/ml to 7.10 U/ml) as compared to one variable at a time (OVAT) design. Interaction effects of the factors individually and in combination can be evaluated by using Taguchi method design of experiment.